A simple modeling approach to elucidate the main transport processes and predict invasive spread: River‐mediated invasion of Ageratina adenophora in China. Issue 12 (31st December 2014) - Horvitz, Nir; Wang, Rui; Zhu, Min; Wan, Fang‐Hao; Nathan, Ran
Abstract: A constantly increasing number of alien species invade novel environments and cause enormous damage to both biodiversity and economics worldwide. This global problem is calling for better understanding of the different mechanisms driving invasive spread, hence quantification of a range of dispersal vectors. Yet, methods for elucidating the mechanisms underlying large‐scale invasive spread from empirical patterns have not yet been developed. Here we propose a new computationally efficient method to quantify the contribution of different dispersal vectors to the spread rate of invasive plants. Using data collected over 30 years regarding the invasive species Ageratina adenophora since its detection at the Sichuan province, we explored its spread by wind and animals, rivers, and roads into 153 subcounties in the Sichuan, Chongqingshi, and Hubei provinces of China. We found that rivers are the most plausible vector for the rapid invasion of this species in the study area. Model explorations revealed robustness to changes in key assumptions and configuration. Future predictions of this ongoing invasion process project that the species will quickly spread along the Yangtze River and colonize large areas within a few years. Further model developments would provide a much needed tool to mechanistically and realistically describe large‐scale invasive spread, providing insights into the underlying mechanisms and an ability to predict future spatial invasive dynamics. Key Points: We present new simple method to examine spread rate by various dispersal vectors Spread by three dispersal vector types quantified by 153 subcounties arrival time The extremely fast invasion of a plant species is attributed to dispersal by rivers